Expression and cell distribution of the intercellular adhesion molecule, vascular cell adhesion molecule, endothelial leukocyte adhesion molecule, and endothelial cell adhesion molecule (CD31) in reactive human lymph nodes and in Hodgkin's disease. - Ruco, L. P. (1992)
The immunocytochemical expression of intercellular adhesion molecule (ICAM-1), vascular cell adhesion molecule (VCAM-1), endothelial leukocyte adhesion molecule (ELAM-1), endothelial cell adhesion molecule (EndoCAM CD31), and HLA-DR antigens was investigated in sections of 24 reactive lymph nodes and in 15 cases of Hodgkin's disease. ICAM-1 was detected in sinus macrophages, follicular dendritic reticulum cells (FDRCs), interdigitating reticulum cells (IDRCs), epithelioid macrophages, Hodgkin's cells (HCs), and vascular endothelium. ICAM-1 expression was often associated with that of HLA-DR antigens. VCAM-1 was detected in FDRCs, in fibroblast reticulum cells (FRCs), in macrophages, and in rare blood vessels. EndoCAM (CD31) was constitutively expressed in all types of endothelial cells, sinus macrophages, and in epithelioid granulomas. ELAM-1 was selectively expressed by activated endothelial cells of high endothelium venules (HEVs). When expression of the inducible adhesion molecules ICAM-1, VCAM-1 and ELAM-1 was comparatively evaluated in HEVs, it was found that ICAM-1 + HEVs were present in all reactive and HD nodes, whereas ELAM-1 and/or VCAM-1 were expressed only in those pathologic conditions characterized by high levels of interleukin-1/tumor necrosis factor (IL-1/TNF) production, such as granulomatosis and Hodgkin's disease. In Hodgkin's disease, the expression of ELAM-1/VCAM-1 was more pronounced in cases of nodular sclerosis and was associated with a significantly higher content of perivascular neutrophils.